The Information and Communication Revolution and the Path of Democratic Transformation in the Arab Region - achour, salim (Journal of Social Sciences and Humanities, 2016)
The study aims to examine the correlational relationship between the information and communication revolution on one hand, and democratic transformation on the other. Stemming from this general objective is a set of goals focused on the influence exerted by the most prominent manifestations of the communication and information revolution (satellite channels, the Internet, etc.) on the formation of public opinion, human rights organizations, and other entities. These factors ultimately lead to achieving democracy or building democratic systems in the Arab region.